The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1475-2891-13-49
|View full text |Cite
|
Sign up to set email alerts
|

The role of meal viscosity and oat β-glucan characteristics in human appetite control: a randomized crossover trial

Abstract: BackgroundFoods that enhance satiety can help consumers to resist environmental cues to eat, and improve the nutritional quality of their diets. Viscosity generated by oat β-glucan, influences gastrointestinal mechanisms that mediate satiety. Differences in the source, processing treatments, and interactions with other constituents in the food matrix affect the amount, solubility, molecular weight, and structure of the β-glucan in products, which in turn influences the viscosity. This study examined the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 53 publications
(59 reference statements)
5
56
0
2
Order By: Relevance
“…Thus, vagal nerve stimulation from other regions of the digestive tract, such as stomach and small intestine, are more likely contributors to modulating diet intake, especially when barley b-glucan can increase digesta viscosity in the upper gut (Brockman et al 2012) and tends to slow the rate of gastric emptying (Belobrajdic et al 2015). These observations align with clinical studies which showed that oat b-glucan increased perceptions of satiety during the postprandial period Juvonen et al 2009;Lyly et al 2010;Pentikainen et al 2014;Rebello et al 2013Rebello et al , 2014 and modulated the secretion of satiety hormones in the small intestine, including cholecystokinin, ghrelin and peptide YY Vitaglione et al 2009). Therefore, b-glucan fermentation in the large bowel is unlikely to contribute to reduced energy intake and body weight.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, vagal nerve stimulation from other regions of the digestive tract, such as stomach and small intestine, are more likely contributors to modulating diet intake, especially when barley b-glucan can increase digesta viscosity in the upper gut (Brockman et al 2012) and tends to slow the rate of gastric emptying (Belobrajdic et al 2015). These observations align with clinical studies which showed that oat b-glucan increased perceptions of satiety during the postprandial period Juvonen et al 2009;Lyly et al 2010;Pentikainen et al 2014;Rebello et al 2013Rebello et al , 2014 and modulated the secretion of satiety hormones in the small intestine, including cholecystokinin, ghrelin and peptide YY Vitaglione et al 2009). Therefore, b-glucan fermentation in the large bowel is unlikely to contribute to reduced energy intake and body weight.…”
Section: Discussionsupporting
confidence: 81%
“…There is growing evidence to suggest that oat β-glucan increases satiety (Beck, et al 2009; Geliebter, et al 2015; Geliebter, et al 2014; Juvonen, et al 2009; Lyly, et al 2010; Pentikainen, et al 2014; Rebello, et al 2014; Rebello, et al 2013) and reduces post-prandial glycemia (Tosh 2013). The most likely mechanism is the viscosity generated in the gastrointestinal tract which has physiologic responses such as delayed gastric emptying, increased stomach distension, delayed intestinal transit, and reduced absorption of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these effects are satiety signals that inhibit hunger after a meal is eaten (Blundell, et al 1996). There is substantial evidence to suggest that oat β-glucan increases satiety (Beck, et al 2009; Geliebter, et al 2015; Geliebter, et al 2014; Juvonen, et al 2009; Lyly, et al 2010; Pentikainen, et al 2014; Rebello, et al 2014; Rebello, et al 2013) and that oat products reduce the human glycemic response, compared to similar wheat foods or a glucose control (Tosh 2013). Further, certain polyphenols such as the anthocyanins found in berries exhibit an insulin-like effect to influence starch degradation and thereby the post meal blood glucose response (McDougall and Stewart 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The oat flakes presented the highest swelling and the largest particle size (Table 2). In addition, whatever the kilning and flaking processes, they contain β-glucan, a major component of oat endosperm cell walls, which probably immobilized some water during the batter preparation and pie baking (Rebello et al, 2014), contributing a drier, harder texture. In fact TPA hardness and chewiness, and Fmax and deformability from the penetration test appeared very near in the same quadrant (Fig.…”
Section: Flash Profile (Fp)mentioning
confidence: 99%